Perubahan Tingkat Konsumsi Sayur dan Buah pada Remaja Melalui Intervensi Media Audio Visual - Hendrik David Julianus Borolla (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The benefits of consuming fruit and vegetables include reducing hypertension, preventing coronary heart disease, stroke, cancer, weight gain and Alzheimer's. This research aims to determine the influence of audiovisual media and lecture methods on changes in fruit and vegetable consumption behavior among teenagers in Gorontalo Regency. This type of research is quantitative with a quasi-experimental research design with a Nonequivalent Control Group Design research design. The respondents used were 76 respondents consisting of 38 respondents for intervention and 38 respondents as controls obtained by purposive sampling. The instruments used were questionnaires, leaflets and audiovisual. Data analysis used univariate analysis. Univariate analysis of food consumption frequency before the intervention showed that 14 people (36.8%) consumed bananas, 24 people (63.2%), 24 people (63.2%) consumed bananas, 26 people (68.4%) and tomatoes (42.1%). %), and after the intervention, bananas were 21 people (55.3%), papaya 31 people (81.6%), kale 30 people (78.9%), and tomatoes 25 people (65.8%). The results of the study used the Wilcoxon test which showed that there was an influence of counseling on behavior change. The results of the Mann-Whitney Test showed differences in behavior in the intervention group and the control group.